Weather observation and forecasting using radiosonde - Jeyaraj Jency Joseph; Rajasekaran Meenal; Francis Thomas Josh; Prawin Angel Michael; Vinoth Kumar Krishnamoorthy; Giriprasad Chandran; Selve Veerabathran (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
Weather balloons are high-altitude meteorological balloons particularly used for carrying scientific payloads into the upper atmosphere. These data are obtained by using an instrument called as radiosonde which is attached to the helium filled weather balloon to measure the meteorological data as it ascends up into the atmosphere. For more than 100 years, weather balloons have given valuable information for climate and meteorological research. In this paper, the radiosonde module is designed with negligible risk of failure and cost effectiveness. The instruments to be fixed along with the weather balloon are logging camera, temperature sensor, pressure sensor, humidity sensor, global positioning system (GPS) module and a power source. This module is used to measure and log the basic weather parameters such as pressure, temperature, humidity and this also captures the picture of a particular locality with the help of a microcontroller. This proposed work is useful for observing high altitude weather data which is essential for predicting natural disasters. Further more, it is helpful to analyze the climatological and weather details of a particular region it also plays an important role in estimating agricultural models.